ELISpot for measuring human immune responses to vaccines. (March 2011) - Slota, Meredith; Lim, Jong-Baeck; Dang, Yushe; Disis, Mary L
The enzyme-linked immunosorbent spot (ELISpot) assay is one of the most commonly used methods to measure antigen-specific T cells in both mice and humans. Some of the primary reasons for the popularity of the method are that ELISpot is highly quantitative, can measure a broad range of magnitudes of response and is capable of assessing critical cellular immune-related activities such as IFN-γγ secretion and granzyme B release. Furthermore, ELISpot is adaptable not only to the evaluation of a variety of T-cell functions, but also to B cells and innate immune cells. It is no wonder that ELISpot has evolved from a research tool to a clinical assay. Recent Phase I and II studies of cancer vaccines, tested in a variety of malignancies, have suggested that ELISpot may be a useful biomarker assay to predict clinical benefit after therapeutic immune modulation. This article will discuss the most common applications of ELISpot, overview the efforts that have been undertaken to standardize the assay and apply the method in the analysis of human clinical trials, and describe some important steps in the process of developing a clinical-grade ELISpot.